Medbesedilni vidik Jančarjevih romanov Drevo brez imena in To noč sem jo videl - Potisk, Martina (Slavia Centralis, 2020)
The intertextual aspect of the novels by Drago Jančar The Nameless Tree and I Saw Her That NightThe paper deals with selected intertextual elements in the novels by Drago Jančar Drevo brez imena (The Nameless Tree, 2008) and To noč sem jo videl (I Saw Her That Night, 2010), thereby specifically focuses on the function of the motto, the signification of the reliance on folk literature, literary references, expressed by the montage and borrowing, and the inclusion of the metric quote in the textual context. Special attention is given to the parts of templates, to which intertextual references are related, and their role in creating a comprehensive image of the main characters and contributing to the ideaed-thematic base of the novels.
Keywords: contemporary Slovenian novel; Drago Jančar; The Nameless Tree; I Saw Her That Night; intertextuality; analysis